The barn eaudiobook The secret history of a murder in mississippi. - Thompson, Wright (Books on Tape, 2024)
The instant New York Times bestseller • Named a Best Book of the Year by The Washington Post , Slate , Vanity Fair , TIME , Buzzfeed , Smithsonian , BookPage , KCUR , Kirkus , and Boston Globe “It literally changed my outlook on the world…incredible.” —Shonda Rhimes "The Barn is serious history and skillful journalism, but with the nuance and wallop of a finely wrought novel … The Barn describes not just the poison of silence and lies, but also the dignity of courage and truth.” — The Washington Post “The most brutal, layered, and absolutely beautiful book about Mississippi, and really how the world conspired with the best and worst parts of Mississippi, I will ever read…Reporting and reckoning can get no better, or more important, than this.” —Kiese Laymon “An incredible history of a crime that changed America.” —John Grisham "With integrity, and soul, Thompson unearths the terrible how and why, carrying us back and forth through time, deep in Mississippi—baring sweat, soil, and heart all the way through.” —Imani Perry A shocking and revelatory account of the murder of Emmett Till that lays bare how forces from around the world converged on the Mississippi Delta in the long lead-up to the crime, and how the truth was erased for so long Wright Thompson’s family farm in Mississippi is 23 miles from the site of one of the most notorious and consequential killings in American history, yet he had to leave the state for college before he learned the first thing about it. To this day, fundamental truths about the crime are widely unknown, including where it took place and how many people were involved. This is no accident: the cover-up began at once, and it is ongoing. In August 1955, two men, Roy Bryant and J.W. Milam, were charged with the torture and murder of the 14-year-old Emmett Till in Money, Mississippi. After their inevitable acquittal in a mockery of justice, they gave a false confession to a journalist, which was misleading about where the long night of hell took place and who was involved. In fact, Wright Thompson reveals, at least eight people can be placed at the scene, which was inside the barn of one of the killers, on a plot of land within the six-square-mile grid whose official name is Township 22 North, Range 4 West, Section 2, West Half, fabled in the Delta of myth as the birthplace of the blues on nearby Dockery Plantation. Even in the context of the racist caste regime of the time, the four-hour torture and murder of a Black boy barely in his teens for whistling at a young white woman was acutely depraved; Till’s mother Mamie Till-Mobley’s decision to keep the casket open seared the crime indelibly into American consciousness. Wright Thompson has a deep understanding of this story—the world of the families of both Emmett Till and his killers, and all the forces that aligned to place them together on that spot on the map. As he shows, the full horror of the crime was its inevitability, and how much about it we still need to understand. Ultimately this is a story about property, and money, and power, and white supremacy. It implicates all of us. In The Barn , Thompson brings to life the small group of dedicated people who have been engaged in the hard, fearful business of bringing the truth to light. Putting the killing floor of the barn on the map of Township 22 North, Range 4 West, Section 2, West Half, and the Delta,...